Rapid liquid-liquid extraction of thallium(III) from succinate media with 2-octylaminopyirdine in chloroform as the extractant - Mahamuni, Sandip V.; Wadgaonkar, Prakash P.; Anuse, Mansing A. (Journal of the Serbian Chemical Society, 2008)
A simple solvent extraction study of thallium(III) was conducted. Selective and quantitative extraction of thallium(III) by 2-octylaminopyridine (2-OAP) in chloroform occurred from aqueous sodium succinate medium (0.0075 M) at pH 3.0. Thallium(III) was back extracted with acetate buffer (pH 4.63). The effect of the concentration of succinate and 2-OAP, the role of various diluents, stripping agents, loading capacity of 2-OAP, equilibrium time and aqueous:organic volume ratio on the extraction of thallium(III) was studied. The stoichiometry of the extracted species was determined based on the slope analysis method and found to be 1: 2: 1 (metal: acid: extractant). The temperature dependence of the extraction equilibrium constant was also examined to estimate the apparent thermodynamic functions Delta H, Delta G and Delta S for the extraction reaction. The method is free from interference of a large number of cations and anions. The method was used for the selective extraction of thallium(III) from its binary mixture with Zn(II), Cd(II), Hg(II), Bi(ill), Pb(II), Se(IV), Te(IV), Sb(III), Ga(III), In(III), AI(III), TI(I) and Fe(III). The proposed method was applied to the synthetic mixtures and alloys. It is simple, selective, rapid and eco-friendly.
Keywords: 2-OAP; liquid-liquid extraction; succinate media; Temperature effect; thallium(III)